Evaluación de los ingresos y gastos del presupuesto institucional en el Ministerio de Agricultura y Ganadería-Babahoyo durante el ejercicio fiscal 2021. - Villasagua Macias, Iris Gabriela (2022)
The Ministry of Agriculture and Livestock is the institutional entity of the Ecuadorian state. They manage their budgets based on institutional planning. This planning leads to defining the type of investment, the source of financing for the resources, and the destination given to these resources. In general, it seeks to meet the needs of the collective, and in the Ministry of Agriculture and Livestock (MAGAP) the projects are aimed at promoting agricultural production and thereby improving the economy of small and medium farmers. The evaluation of the income and expenses of the budget to which the present investigative work refers, allows to guide and identify if the resources were used as planned and also allows to assess the fulfillment of its execution during the fiscal year 2021.